c.1 - Chadha, S.K. (ed.) (Delhi, 1988)
The Himalayan ecosystem is one of the most vital and interesting. It supports more than 150 million people in its shadow. The mighty and magnificent rivers which are closely associated with the hoary past of the Indian culture arise in these mountains. Steeped in age old traditions.
Keywords: Ecology-Himalayas